2018
DOI: 10.12659/pjr.899684
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Structural Changes in Post-Stroke Hemiplegic Shoulders

Abstract: SummaryBackgroundStroke and hemiplegia are frequent complications of stroke. This study was performed to sonographically evaluate post-stroke hemiplegic shoulders and explore possible relationship(s) between the sonographic findings and clinical indices.Material/MethodsForty-five stroke patients and 45 age- and sex-matched controls were recruited. Standard sonographic examination of both shoulders was performed to assess for joint subluxation, rotator cuff tears, tendinosis, subacromial-subdeltoid bursitis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…22 Comparing our results with this study, all the patients in group A (suprascapular nerve block group) experienced significant pain relief, confirming the efficacy of this procedure in hemiplegic shoulder pain. A number of studies have reported that rotator cuff tendinitis is present in almost 33% of stroke survivors with hemiplegia, 23,24 Hence, it is considered prudent to avoid multiple intraarticular steroid injections in hemiplegic patients, especially as they are known to cause atrophy in tendons and ligaments. A comparison of intraarticular steroid injection versus suprascapular nerve block for non-specific shoulder pain reported that both interventions resulted in improvement in pain scores, with negligible difference in terms of overall efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…22 Comparing our results with this study, all the patients in group A (suprascapular nerve block group) experienced significant pain relief, confirming the efficacy of this procedure in hemiplegic shoulder pain. A number of studies have reported that rotator cuff tendinitis is present in almost 33% of stroke survivors with hemiplegia, 23,24 Hence, it is considered prudent to avoid multiple intraarticular steroid injections in hemiplegic patients, especially as they are known to cause atrophy in tendons and ligaments. A comparison of intraarticular steroid injection versus suprascapular nerve block for non-specific shoulder pain reported that both interventions resulted in improvement in pain scores, with negligible difference in terms of overall efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is a relatively established tool for assessing post-stroke hemiplegic shoulders ( 19 ) . Furthermore, it has important comparative advantages in evaluating shoulder subluxation ( 6 , 7 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MU examination is sensitive in detecting SA-SD bursal effusion or inflammation in patients with HSP. [ 24 ] Furthermore, hemiplegic patients primarily suffer from adduction and intorsion of the upper limbs. Under external traction, uncoordinated muscle movements can cause uneven stress on the intertubercular sulcus.…”
Section: Discussionmentioning
confidence: 99%